Effectiveness of Tai Chi Exercise on VO2max in Patients with Cancer after Chemotherapy: An Experimental Study - Seema Das; Somyata C Satpathy Sarma; Subarna Sankar Das; Trishna Kakati (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Tai Chi, originally a Chinese martial art, is now recognised as an effective form of aerobic exercise beneficial for cardiac rehabilitation and mental well-being. It involves gentle movements, deep breathing, and relaxation, promoting body awareness and focus. Classified as a moderate-intensity exercise (2.6-6.5 MET), Tai Chi has shown clinical benefits, particularly for individuals with chronic conditions. Aim: This study aimed to evaluate the effectiveness of Tai Chi exercises by comparing baseline and post-exercise VO2max scores in cancer patients after chemotherapy. Materials and Methods: A quasi-experimental study commenced in March 2022 and was completed in September 2022, affiliated with the College of Physiotherapy and Medical Sciences under Srimanta Sankaradeva University of Health Sciences, Guwahati, Assam, India. A total of 30 subjects were assessed, of whom sevenwere excluded, two declined, and 21 participated. After seven dropouts, 15 participants (aged 20-60 years, diagnosed with breast, stomach, or colorectal cancer) at stage II who had completed all doses of chemotherapy completed a 6-week Tai Chi programme (30-minute sessions twice a week). VO2max was measured pre- and post-intervention. Demographic data (gender, height, weight, cancer type, chemotherapy doses, and vital signs) were considered. SPSS software version 25 was used, the Shapiro-Wilk test for normality was applied, and a paired t-test was conducted for parametric analysis, with statistical significance set at p<0.05, where p<0.001 was considered highly significant. Results: Fifteen post-chemotherapy patients participated in a 6-week Tai Chi programme. Pre- and post-programme VO2max values were analysed using paired sample t-tests, with the Shapiro-Wilk test for normality. The sample consisted of 33% males and 67% females, with a mean age of 42.8 years (SD=8.41). VO2max increased from a pre-exercise mean of 32.92 to a post-exercise mean of 36.64. Statistical analysis in SPSS version 25 showed significant improvement (p<0.001). Conclusion: The study indicates that a 6-week Tai Chi exercise programme significantly improves VO2max in cancer patients post-chemotherapy, suggesting its potential as an effective rehabilitative intervention for enhancing cardiovascular fitness and overall well-being in this population.